Keputusan Mahasiswa Universitas “X” Bandung Untuk Merokok Di Lingkungan Kampus Yang Dipengaruhi Oleh Faktor Sosial - Ayuningtyas Hapsari; Alfath Haikal Muhammad (Ultima Management : Jurnal Ilmu Manajemen, 2018)
Indonesia is the country with the highest number of teen smokers in the world. About 80% of smokers in Indonesia start the habit before the age of 19 years. Based on the results of a pre-survey of 10 students that there are still many who violate the rules despite the existing prohibition to not smoke in public places at the University of "X". It also shows a lack of concern for smokers against others who do not smoke. This study aims to look at the influence of social factors on the students decision at the University X Bandung to smoke on campus. This research uses descriptive verification method by distributing questionnaires to 30 students respondents of the University "X" Bandung, and use a Simple Linear Regression analysis methods. Based on the results of regression calculations, the influence of social factors on smoking decisions on campus is very small that is equal to 37.9% while the remaining 62.1% influenced by other variables not examined in this study as a factor from the individual respective smokers, such as: lifestyle, psychological factors and cultural factors. Keywords: Social Marketing, Consumer Behavior, Social Factors and Consumer Buying Decision